Comparison of hematological parameters for signs of anemia among participants with and without chronic periodontitis: A cross-sectional study - Sarita Parihar; N K Sharma; Atul Bhatnagar; Dhiraj Kishore; Ajit V Parihar; Faizia Rahman (Journal of Indian Association of Public Health Dentistry, 2019)
Background: Chronic infection has a known effect on the cytokine levels of the body which adversely affects erythropoiesis. Aim: The aim of this study is to compare hematological parameters among participants with and without chronic periodontitis which also is a known infectious inflammatory disease of the gums. Materials and Methods: Forty patients with severe chronic periodontitis (Group A) and forty periodontally healthy participants (Group B) in the age group of 30–55 years presenting to the Outpatient Department of the Faculty of Dental Sciences, Banaras Hindu University, were recruited in the study and were assessed for various hematological and periodontal parameters. SPSS 17.0 version was used. Student's t-test (unpaired) was used. P < 0.05 was considered statistically significant. Results: Group A showed lower hemoglobin (Hb, 13.47 ± 1.05, P = 0.019), erythrocyte count (4.63 ± 0.40, P = 0.002), and mean corpuscular Hb concentration (32.58 ± 0.90, P = 0.003) values compared to Group B (13.95 ± 0.70, 4.90 ± 0.33, and 33.18 ± 0.81, respectively). Conclusion: Within the limitations of the study, it can be safely deduced that a positive relationship exists between the hematological parameters and severity of chronic periodontal disease, suggesting that long-standing chronic periodontitis may lead to the development of signs of anemia.